2014
DOI: 10.1245/s10434-014-4068-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Thoracoscopic Resection of Stage I and II Thymoma: A Propensity-Matched Study

Abstract: VATS appears feasible for patients with stage I and II thymoma and is associated with better perioperative outcomes than MST. The oncological outcomes are also similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
3
16
1
3
Order By: Relevance
“…Intra operative blood loss in present study was 45±30 ml ,this was in either similar or less when compared to the studies published in the literature. [7][8][9][10] There is sufficient evidence that intra operative blood loss is less in VATS Thymectomy compared to open thymectomy, this fact is supported by findings in our study. Mean operating time in our study was 104 mins with a range of 78 to 145 mins.…”
Section: Discussionsupporting
confidence: 89%
“…Intra operative blood loss in present study was 45±30 ml ,this was in either similar or less when compared to the studies published in the literature. [7][8][9][10] There is sufficient evidence that intra operative blood loss is less in VATS Thymectomy compared to open thymectomy, this fact is supported by findings in our study. Mean operating time in our study was 104 mins with a range of 78 to 145 mins.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous reports (12,38,39), several authors demonstrated the decreased invasiveness of TT for thymoma. Most of the reports in this review revealed that TT showed a significantly shorter post-operative hospital stay, decreased intraoperative blood loss, and fewer complications compared to OT ( Table 2).…”
Section: Surgical Treatmentsupporting
confidence: 93%
“…With regard to the surgical treatment of thymoma, the preferred surgical approach and procedure remain controversial. According to previous reports [5,6], several authors have endorsed less invasive thoracoscopic surgery procedures for thymoma. Pennathur et al [7] reported their surgical results from a comparative study of video-assisted thoracoscopic surgery versus OT for patients with early-stage thymoma.…”
Section: Long-term Survivalmentioning
confidence: 99%